2008
DOI: 10.1038/jhh.2008.59
|View full text |Cite
|
Sign up to set email alerts
|

Fermented lactotripeptides-containing milk lowers daytime blood pressure in high normal-to-mild hypertensive subjects

Abstract: Figure 1 Placebo-corrected change in daytime office blood pressure over 8 h after consumption of lactotripeptide (LTP) milk on days 1 and 29 of intervention (data are presented as LsMean±s.e.m., *Po0.05).What is known about this topic K The fermented milk-derived lactotripeptides (LTP) isoleucyl-prolyl-proline and valine-prolyl-proline have been shown to lower blood pressure over several weeks in hypertensive subjects. 1-9 K LTP have been shown to possess ACE-inhibitory activity in vitro. 11 What this Study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 10 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…The Dietary Approaches to Stop Hypertension trial demonstrated that a dietary pattern abundant in fruits, vegetables and low-fat dairy products can considerably reduce BP (25) . Data from Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Kawase (2000) (8) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Engberink (2008) (15) van der Zander (2008) (16) Jauhiainen (2010) (17) Usinger ( Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Jauhiainen (2010) (17) Usinger (2010 Fig . 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Dietary Approaches to Stop Hypertension trial demonstrated that a dietary pattern abundant in fruits, vegetables and low-fat dairy products can considerably reduce BP (25) . Data from Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Kawase (2000) (8) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Engberink (2008) (15) van der Zander (2008) (16) Jauhiainen (2010) (17) Usinger ( Study Net change 95% CI Weight (%) Hata (1996) (6) Agerholm-Larsen (2000) (7) Inoue (2003) (9) Seppo (2003) (10) Mizushima (2004) (11) Tuomilehto (2004) (12) Aihara (2005) (normotensive) (13) Aihara (2005) (hypertensive) (13) Jauhiainen (2005) (14) Jauhiainen (2010) (17) Usinger (2010 Fig . 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Panel notes that 15 RCTs Cicero et al, 2010;De Leeuw et al, 2009;Engberink et al, 2008;Itakura et al, 2001;Mizushima et al, 2004;Seppo et al, 2003;Tuomilehto et al, 2004;Turpeinen et al, 2009;Usinger et al, 2010a;Van der Zander et al, 2008a;Van der Zander et al, 2008b;Van Mierlo et al, 2009 two studies;Yoshizawa et al, 2010), of which seven were designed to detect small (3-9 mm Hg) differences in SBP De Leeuw et al, 2009;Usinger et al, 2010a;Van der Zander et al, 2008a;Van der Zander et al, 2008b;Van Mierlo et al, 2009 two studies), did not observe an effect of IPP and VPP on SBP or DBP.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 661 183mentioning
confidence: 99%
“…In its earlier opinion (EFSA Panel on Dietetic Products Nutrition and Allergies (NDA), 2009), the Panel had considered one meta-analysis (Xu et al, 2008), which included nine human intervention studies, as well as six additional randomised controlled trials (RCTs) (De Leeuw et al, 2009;Engberink et al, 2008;Hirota et al, 2007;Van der Zander et al, 2008a;Van der Zander et al, 2008b;Van Mierlo et al, 2009) for the scientific substantiation of the claim. The Panel noted in this assessment that although some small studies had observed a significant decrease in systolic blood pressure (SBP) with the administration of lactotripeptides at doses around 5 mg per day in untreated pre-hypertensive or moderately hypertensive subjects, these results have not been supported by large intervention trials providing daily doses of lactotripeptides in the range of 2.7 mg to 14 mg in either normotensive or untreated hypertensive subjects, and concluded that the evidence was insufficient to establish a cause and effect relationship between the consumption of IPP and VPP and maintenance of normal blood pressure.…”
Section: Scientific Substantiation Of the Claimed Effect (Id 661 183mentioning
confidence: 99%
See 2 more Smart Citations